Educational and training organizations management. Requirements to design assessment tasks in the frame of TECO-D research - Cornacchia, Matteo; Sorzio, Paolo (Form@re - Open Journal per la formazione in rete, 2018)
In this contribution, the relevance of the organizational competencies related to the organizational aspects in the educational sector is analysed at two levels. At the first one, the managerial competencies are introduced according to the scientific literature and related to the learning outcomes, as they are expressed by the “Dublin descriptors”. At the second level, the development of the organizational competencies is described in terms of the constructivist perspective, as a process of conceptual change of the informal reasoning strategies the students bring to bear at the outset of their university practice into the higher-order thinking strategies that can be the outcomes of the University-level courses. The characteristics of effective learning environments to promote the organizational competencies are also discussed. Il management delle organizzazioni educative e formative. Condizioni per la costruzione dei test sulle competenze TECO-D In questo contributo si propongono due livelli di analisi della competenza manageriale e organizzativa nell’ambito del lavoro educativo. Al primo livello tali competenze vengono considerate in quanto obiettivo formativo finale della classe di laurea L-19 sulla base dei “descrittori di Dublino” e della letteratura scientifica di settore. Al secondo livello, invece, lo sviluppo della competenza organizzativa viene descritto attraverso la prospettiva costruttivista, ovvero come quel processo che, al termine del percorso universitario, dovrebbe consentire agli studenti di modificare le loro strategie di ragionamento informale in strategie di pensiero di ordine superiore o di tipo “complesso”. In conclusione viene proposta una riflessione su quali ambienti di apprendimento possono promuovere competenze di tipo manageriale e organizzativo.